Epigenetic clock analysis in methamphetamine dependence. (November 2022) - Takemura, Yukihiro; Tanifuji, Takaki; Okazaki, Satoshi; Shinko, Yutaka; Otsuka, Ikuo; Horai, Tadasu; Shirai, Toshiyuki; Aso, Katsuro; Yamamoto, Noriya; Hishimoto, Akitoyo
Highlights: DNA methylation (DNAm) is related to biological aging and health risks. Individuals with methamphetamine (MA) dependence also face these risks. We investigated DNAm age and DNAm-based telomere length (DNAmTL) in them. Patients with MA dependence showed significant acceleration in DNAm age and DNAmTL. MA dependence leads to specific changes in the DNAm of age-predicative factors. Abstract: Methamphetamine (MA) is used worldwide and causes serious public health and social problems. MA affects the central nervous, cardiac, and immune systems, which causes neuropsychiatric and cardiovascular diseases and infection. Epigenetic changes, including DNA methylation (DNAm), are associated with various clinical phenotypes of MA abuse. DNAm is related to biological aging and health risks; hence, we aimed to assess the changes in biological aging in MA dependence using the DNAm age and DNA methylation-based telomere length (DNAmTL). We used five measures of DNAm age (HorvathAge, HannumAge, SkinBloodAge, PhenoAge, and GrimAge), DNAmTL, and DNAm-based age-predictive factors (plasma proteins and blood cell composition). We compared patients with MA dependence and healthy controls ( n  = 24 each) using the DNAm profiles obtained from whole-blood samples. Patients with MA dependence showed significant acceleration in PhenoAge and GrimAge, as well as a trend for significant acceleration in DNAmTL. Following adjustment for confounding factors, MA dependence was significantly associated with accelerations in PhenoAge, GrimAge, and DNAmTL, as well as alterations in DNAm-based age-predictive factors (beta-2-microglobulin, granulocytes, and naive cluster of differentiation 4+ T cells). Our results suggested an acceleration of biological aging and specific changes in the DNAm of age- predictive factors in MA dependence.